The comparative assessment of awareness, perspective, and basic practice skills about the Saudi pharmacovigilance system among students of different health-care professionals of a Saudi Female University - Asmatanzeem Bepari; Rasha Assad Assiri; Maya Abdullah AlYahya; Shaden Jamaan AlGhamdi; Amal Mohammed AlGhamdi; Afrah Asaad AlOnazi (Elsevier, 2020)
Introduction: The low reporting of adverse drug reactions (ADRs) in Saudi Arabia is prevalent among health-care professionals and is responsible for poor ADR signal detection. Therefore, all healthcare institutes connected with patient concern require joint and sustained efforts to strengthen ADR reporting by providing harmless and efficient medication. Objectives of the study: The current study was performed to estimate the awareness corresponding to the knowledge, perspective, and basic practice skills about the Saudi pharmacovigilance system among students of different health-care professionals of a Saudi Female University. Material & methods: A questionnaire was planned and standardized by a thorough literature review. Questions were classified: Group 1 had ten knowledge-based, group 2 five attitude-based, and group 3 four basic practice skills-based questions of pharmacovigilance (PV). Also, determinants that hindered them from becoming part of the pharmacovigilance program were reported. Such 600 questionnaires were distributed among the interns, final and prefinal year students of different health care professionals of Princess Nourah bint Abdulrahman University, Riyadh. The participants' awareness and practice skills were graded in 3 categories as unacceptable, inadequate, and adequate, depending upon the mean score along with identification of their type of perception towards PV. The data was interpreted by calculating the frequencies, one-way ANOVA, and by post-hoc Tukey-Kramer HSD multiple comparison test. Results: Five hundred ninety-two questionnaires were statistically investigated. Students' awareness and basic practice skills of pharmacovigilance were found to be inadequate, but positive perception towards PV. Conclusion: Our study showed that awareness and practice skills of PV among students of different health care professionals stand insufficient but favourable perceptions towards PV. Regular educative interventions can increase these parameters of pharmacovigilance.